Kenneth S. answered • 04/27/16

Tutor

4.8
(62)
Algebra II EXPERT will help you survive & prosper

This is easy, because you are given the starting term, -6. And you are given a formula a

_{n}= a_{n-1}+2n.So let's choose n = 2 so that we can calculate, from the formula, what a

_{2}is. The formula tells us that a_{2}= a_{2-1 }+ 2(2) which means -6 + 4 = -2.Now repeat this, using n = 3, etc... Each term can be computed easily from the prior term--that's the meaning of the subscripts on the a's in the formula.